Tinjauan Sistem Hukum dalam Penerapan Peraturan Daerah (Perda) Syari’ah di Tasikmalaya - Darnela, Lindra (UIN Sunan Kalijaga, 2016)
Tasikmalaya is an area that strives to formalize the Shari'ah in the form of regional regulation. Some rules are made in order to support such efforts. In looking at the effectiveness of the enforcement of the law, the legal system is used as a perspective in this study. The paper looked at the implementation of the Regional Regulation Sya'riat Islam in the three elements of the legal system. Based on the substance of the law, there are several provisions of the regulations that contain bias and allow violence against minorities, such as the word Muslim and misleading. In terms of legal structure, authorities in charge of ensure the entry into force of these regulations, do not seem to serious in performing their duties. Whereas in the case of the legal culture of society Tasikmalaya provide enormous support in the implementation of the Regulation of Islamic Shari'ah. However this issue is reaping the pros and cons.